Crop monitoring system using image processing and environmental data - Rabbi, Shadman; Shabik, Ahnaf (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.